Numerical Investigation on Dynamic Response of RC T-Beams Strengthened with CFRP under Impact Loading - Huiling Zhao; Xiangqing Kong; Ying Fu; Yihan Gu; Xuezhi Wang (Crystals, 2020)
To precisely evaluate the retrofitting effectiveness of Carbon Fiber Reinforced Plastic (CFRP) sheets on the impact response of reinforced concrete (RC) T-beams, a non-linear finite element model was developed to simulate the structural response of T-beams with CFRP under impact loads. The numerical model was firstly verified by comparing the numerical simulation results with the experimental data, i.e., impact force, reaction force, and mid-span displacement. The strengthening effect of CFRP was analyzed from the section damage evaluation. Then the impact force, mid-span displacement, and failure mode of CFRP-strengthened RC T-beams were studied in comparison with those of un-strengthened T-beams. In addition, the influence of the impact resistance of T-beams strengthened with FRP was investigated in terms of CFRP strengthening mode, CFRP strengthening sizes, CFRP layers and FRP material types. The numerical simulation results indicate that the overall stiffness of the T-beams was improved significantly due to external CFRP strips. Compared with the un-strengthened beam, the maximum mid-span displacement of the CFRP-strengthened beam was reduced by 7.9%. Additionally, the sectional damage factors of the whole span of the CFRP-strengthened beam were reduced to less than 0.3, indicating that the impact resistance of the T-beams was effectively enhanced.